Analisis Produktivitas Dan Biaya Alat Berat Pada Penanganan Long Segment Jalan Sapta Marga Kampung Besar Kecamatan Banda Mulia - mahyuddin; Rajib Muammar; Iqbal (Universitas Iskandar Muda, 2026)
Heavy equipment plays an important role in accelerating construction processes and reducing operational costs. Equipment such as dump trucks, motor graders, vibrator compactor rollers, and water tank trucks significantly influence project completion time. However, initial planning often does not match field conditions, resulting in increased costs and delays. Therefore, an analysis of heavy equipment productivity is necessary to ensure efficient utilization and cost optimization. This study aims to analyze the productivity, implementation time, and cost of heavy equipment in the Long Segment Handling Project for routine maintenance, periodic maintenance, and road reconstruction on Jalan Saptamarga – Kampung Besar, Banda Mulia District, specifically for subbase (LPB) and base (LPA) layers over a 1,000-meter section. The analysis of productivity and equipment costs was conducted using the Bina Marga 2023 method. The results show that the productivity of dump trucks is 30.42 m³/day, motor graders reach 975.20 m³/hour for LPB and 989.00 m³/hour for LPA, vibrator compactor rollers achieve 928.20 m³/day for LPB and 702.84 m³/day for LPA, while water tank trucks reach 450.00 m³/day. The LPB work requires 3 working days using 14 dump trucks and one unit each of motor grader, compactor roller, and water tank truck. Meanwhile, LPA work is completed in 2 days using 12 dump trucks and one unit of each supporting equipment. The rental costs per day are Rp 2,356,235.39 for dump trucks, Rp 3,467,735.73 for motor graders, Rp 2,846,290.20 for vibrator compactor rollers, and Rp 2,367,435.18 for water tank trucks. The total equipment rental cost is Rp 125,006,269.65 for LPB and Rp 73,912,571.55 for LPA, resulting in an overall cost of Rp 198,918,841.20.